The Social Origins of Effort: How Incentives Reduce Socioeconomic Disparities among Children. - Radl, Jonas; Foley, William; Kröger, Lea Katharina; Lorente, Patricia; Palacios-Abad, Alberto; Solga, Heike; Stuhler, Jan; Swarr, Madeline (American Sociological Review, 2026)
Cognitive effort (i.e., the mobilization of mental resources for task performance) is essential to equality of opportunity and meritocracy because it epitomizes individual agency. However, sociological theories of social inequality in effort are scarce and partial, and available empirical measures of effort are unreliable and lack validity. We fill this lacuna by (1) elaborating a theoretical account of how socioeconomic status (SES) affects children's cognitive effort, (2) developing a novel research design for measuring effort using simple-yet-demanding behavioral tasks and varying incentive conditions, and (3) presenting evidence based on this laboratory design featuring 1,360 5th-grade students. We theorize that greater material abundance and lower environmental threat reduce the subjective costs of exerting effort for higher-SES children, and that parental socialization emphasizing autonomy gives them more intrinsic motivation compared to lower-SES children. Conversely, we posit that the effort of lower-SES children is more susceptible to material and status rewards. Supporting our expectations, we find that social origin effects on effort are largest when incentives are absent, yet decrease notably when material incentives are introduced. Albeit surprisingly modest and malleable, social origin effects on effort challenge voluntaristic notions of individual agency. Crucially though, providing tangible performance rewards can significantly narrow socioeconomic disparities in effort.